Aplikasi Pengaman Kendaraan Berbasis Mikrokontroler ATmega 8 and ATtiny 2313 - Santoso Setiawan (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2017)
One of the concerns experienced by the people today is rampant theft of the vehicle. It takes a system or a good security tools to complement existing security model. With the advancement of technology, it can be made a vehicle safety system uses a combination of numbers based microcontroller ATmega 8 and ATtiny 2313. The system is mounted on a vehicle and a series of combinations of numbers inputted through the remote, so it can provide a solution to the problem of theft of the vehicle